Iteration vs Recursion in Introduction to Programming Classes: An Empirical Study - Sulov, Vladimir (Cybernetics and information technologies : CIT, 2016)
In this article we have presented the results of an empirical study which was carried out on 130 students in Introduction to programming classes. Their initial preference, success rate, comprehension and subsequent preference were studied when dealing with programming tasks which could be solved using either iteration or recursion.